Bioconcentration Factor (BCF) and Translocation Factor (TF)of Heavy Metals in Mangrove Trees of Blanakan Fish Farm - Takarina, Noverita Dian; Pin, Tjiong Giok (Makara Journal of Science, 2017)
In the mangrovesof Blanakan, Indonesia, silvofishery practices may play arole in maintaining the environmental quality of ponds. Mangroves are known as pollutant traps since their root systems absorb and accumulate materials. Heavy metals are pollutants that often contaminate aquatic environment like ponds. The bioconcentration factor can be used to evaluate the content of heavy metals in organisms, while the translocation factor can be used to measure the amount of heavy metals transferred form one organ to another. The aim of this study was to determine the bioconcentration factor and the translocation factor of heavy metals (Pb, Cu,andZn) in mangrovetrees (Avicennia and Rhizopora) at the Blanakan ponds. Samples of mangrove trees from 3 stations, were cut using a knife, and samples of sediments were collected using Ekman Bottom Grab sampler. Samples were then prepared for heavy metal content analysis using the Shimadzu 6300 atomic absorption spectrophotometer. The bioconcentration and translocation factorswere calculated using formulas; the bioconcentration factor was calculated as the content of heavy metals in trees divided by the content of heavy metals in sediments. Results showed that the bioconcentration factor of Cu was higher than 1 in the roots, stems and leaves of Avicennia trees and of Zn was higher than 1 in the roots of Rhizopora trees at station 1. Translocation factors higher than 1 were mostly found in Avicennia (Cu) and Rhizopora (Pb) trees. Mangrove trees with translocation values of greater than 1 for one or more heavy metals can be considered as strong accumulators of the corresponding metals.